Evaluating the Strength Characteristics of Clay- Gravel Mixtures - Akinleye, M. T.; Salami, L. O.; Salami, M. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Shear strength is one of the most important soil properties in almost all geotechnical engineering problems. Therefore, this study was aimed at investigating the effect of gravel on the shear strength of clayey soil. Two clayey soil samples were obtained from a dug pit from different locations in Osogbo, Osun State and the gravels were collected locally. Three different gradations of gravel (2-6mm, 6-12mm, and 12-20 mm) were mixed in a dry state in percentages of 5, 10, 15, 20, 30, 40 and 50% with the collected clay soil respectively. Initially, some physical properties of clayey soil and the gravel, which include specific gravity, particle size analysis, liquid limit and plastic limit, were determined in accordance with BS 1377-3:2018. Consequently, the California Bearing Ratio (CBR) and Consolidated - Undrained (CU) triaxial compression tests at three different confining pressures of 50, 100 and 150 kN/m2, with a loading rate of 0.5 mm/min were carried out on the clay-gravel mixtures in accordance with BS 1377 (1990). The results from the CBR test indicated that the CBR value of the clay-gravel mixtures was higher than that of pure clay. The result of shear strength showed that the cohesion and effective angle of internal friction increases as the concentration of gravel increases from 0 to 50%. As the gravel size was increased from 6-12mm, effective cohesion reduces and angle of internal friction increases.  It concluded that locally available gravel can be used to improve the strength properties of clayey soil for engineering construction.